(untitled) (Research, Society and Development, 2022)
Prematurity, defined as a child born with a gestational age of fewer than 37 weeks, is a complex clinical syndrome with multiple etiological factors and is linked to a wide range of clinical conditions correlated with survival and pattern of growth and development. The study aimed to identify the profile of mothers and preterm infants born alive in a maternity hospital in the Sergipe’s State interior. A retrospective, cross-sectional and epidemiological investigation was conducted. Data was acquired from the information system on live births (SINASC) based on the declarations of live births. Main findings: Maternal age group (28.5% were between 20 and 24 years old, 27.3% between 25 and 29 years old, and 20.2% were between 10 and 19 years old); Marital status (70.4% of the mothers had a consensual union; 14.9% are married; 12.7 are single; the others are legally separated, widows or who ignored them, representing 1.1% (p < 0.05); Adequacy of prenatal care (most pregnancies had prenatal care classified as more than adequate, 68.5% of women had 7 or more prenatal consultations (p < 0.05); APGAR of newborns ( most presented scores between 8 to 10, in the first and fifth minutes of life (p < 0.05)). The data from this study highlights the importance of identifying the main risk factors for premature birth, reaffirming the importance of prenatal care started early. Furthermore, pregnant women who are in a consensual relationship or who are married have a lower rate of premature births, therefore knowing their profile is crucial. In conclusion, proper prenatal care, when started early, can assist in detecting and preventing the main reasons for premature birth.